Corrigendum to “Reno- and hepato-protective effect of allopurinol after renal ischemia/reperfusion injury: Crosstalk between xanthine oxidase and peroxisome proliferator-activated receptor gamma signaling” [Food Chem. Toxicol. 178 (2023) 113868] - Eman Soliman; Shimaa Mustafa Elshazly; Samar M. Shewaikh; Fatma El-shaarawy (Food and Chemical Toxicology, 2025)

Potential use of bacteriophages as biocontrol agents against multidrug-resistant pathogens in wastewater treatment: a review - Samar Ragab; Mohamed Kamal Mustafa; Yara Y. Hassan; Alaa Nasr; Bassant H. Abd El Hady; Ayman El-Shibiny (Environmental Sustainability, 2024)
The conventional methods of wastewater treatment are essentially used to remove contaminants and pathogens from wastewater before it is released into the environment or used for other purposes. With the increasing number of Multidrug-Resistant (MDR) organisms in wastewater, the potential usefulness of conventional treatment methods has been re-evaluated. The conventional biological treatment and disinfection have been proven in many studies to increase the prevalence of Antibiotic Resistance Genes (ARG) in bacteria. More than 25 genes responsible for antibiotic resistance were found to be increased from influent to effluent in different Wastewater Treatment Plants (WWTPs). Additionally, many studies have discussed the high abundance of several Mobile Genetic Elements (MGEs) after disinfection by chlorination and ozonation. Bacteriophage-based therapy has emerged as an innovative method for effectively managing microorganisms in wastewater treatment and in various other applications. Bacteriophages can be utilized to kill pathogenic bacteria and eradicate the biofilms formed by the bacteria in wastewater treatment plants with low intrinsic toxicity. However, the use of bacteriophages has been associated with some limitations, including the narrow host range spectrum. This review provides a critical overview of the recent knowledge on the effect of biological treatment and disinfection on spreading antibiotic resistance. In addition, we highlight the interactions among bacteria and phages to sustain the water treatment process. We also emphasize the proposed improvement in wastewater treatment using bacteriophage-based therapy. Our focus is identifying gaps, opportunities, and critical concerns that should be addressed in further research.

Acrylamide toxicity in aquatic animals and its mitigation approaches: an updated overview - Mohammed A. E. Naiel; Samar S. Negm; Shakira Ghazanfar; Arshad Farid; Mustafa Shukry (Environmental Science and Pollution Research, 2023)
Acrylamide (ACR) is widely applied in various industrial activities, as well as in the water purification process. Furthermore, ACR is synthesized naturally in some starchy grains exposed to high temperatures for an extended time during the cooking process. Because of its widespread industrial usage, ACR might be released into water stream sources. Also, ACR poses a high risk of contaminated surface and ground-water resources due to its high solubility and mobility in water. Furthermore, animal studies have indicated that ACR exposure may cause cancer (in many organs such as lung, prostate, uterus, and pancreas), genetic damage (in both somatic and germ cells), and severe effects on reproduction and development. Recently, numerous studies have shown that ACR has a mild acute cytotoxic impact on aquatic species, particularly during early life stages. Besides, wide-spectrum usage of ACR in many industrial activities presented higher environmental risks as well as major hazards to consumer health. This literature was designed to include all potential and accessible reports on ACR toxicity related with aquatic species. The Preferred Reporting Items for Systematic Reviews were applied to evaluate the risk effects of ACR on aquatic organisms, the ACR sub-lethal concentration in the ecosystem, and the possible protective benefits of various feed additives against ACR toxicity in fish. The major findings are summarized in Tables 2 and 3. The primary aim of this literature was to specify the hazards of ACR toxicity related with fish welfare and possible suggested strategies to reduce its risks.

Reno- and hepato-protective effect of allopurinol after renal ischemia/reperfusion injury: Crosstalk between xanthine oxidase and peroxisome proliferator-activated receptor gamma signaling - Eman Soliman; Shimaa Mustafa Elshazly; Samar M. Shewaikh; Fatma El-shaarawy (Food and Chemical Toxicology, 2023)

The involvement of antioxidant, stress, and immune-related genes in the responsive mechanisms of common carp (Cyprinus carpio) to hypersalinity exposure - Hassan Ahmed; Karima A. Bakry; Ahmed Abdeen; Halla E. K. El bahgy; Mohamed Abdo; Florin Imbrea; Liana Fericean; Mona A. Elshemy; Samah F. Ibrahim; Mustafa Shukry; Samar H. Baloza; Walaa F. A. Emeish (Frontiers in Marine Science, 2023)
Salinity stress is one of the marked influencing factors on the ecophysiology of aquaculture and is considered an important reason for the retreat of the fish industry. The current study is an endeavor to elucidate the molecular mechanisms that underlie the response to salinity stress in common carp. Fish (Average weight 5 ± 2 g) were randomly distributed into two groups; the 1 st is a control was exposed to tap water (0.2 ppt salinity) and the 2 nd is a treated was exposed to hypersalinity (10 ppt salinity) for five days. Serum biochemical indicators including total protein, albumin, globulins, A/G ratio, blood glucose, cortisone, Na + , K + , and Cl - levels were evaluated. Besides, Tumor necrosis factor-α, interleukin-1β, corticotropin-releasing hormone, and catalase enzyme mRNA expression levels were assessed in lymphoid and immunocompetent organs (liver and spleen) and osmoregulatory organs (kidney and gills) by using Real-time qPCR. Hypersalinity adversely affected the biochemical markers; total protein, albumin, and globulins decreased significantly; however, blood glucose, serum cortisol, and sodium markedly increased in fish exposed to hypersalinity compared with the control. In addition, from the molecular point of view, all the evaluated genes were upregulated at a high expression rate in the liver compared with other studied organs after the salinity challenge. On the contrary, hypersalinity modulated the expression of immune-related genes (Tumor necrosis factor-α and interleukin-1β) in the kidney and spleen and upregulated corticotropin-releasing hormone mRNA in all studied organs except gills. In conclusion, the obtained data clarified the molecular and biochemical mechanisms of salinity stress on the liver, kidney, spleen, and gills. Furthermore, it strongly suggests the implication of neural, endocrine, and immune systems in the responsive mechanisms to the salinity stress in carp.

Natural metabolites from the soft coral Nephthea sp. as potential SARS-CoV-2 main protease inhibitors - Omnia Hesham Abdelhafez; John Refaat Fahim; Muhamad Mustafa; Asmaa M. AboulMagd; Samar Yehia Desoukey; Alaa M. Hayallah; Mohamed Salah Kamel; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Plant growth promoting rhizobacteria in sustainable agriculture: from theoretical to pragmatic approach - Samar Mustafa; Saba Kabir; Umbreen Shabbir; Rida Batool (Symbiosis, 2019)